Research Note: Application of reverse-transcription recombinase-aided amplification-lateral flow dipstick method in the detection of infectious bursal disease virus - Chao Wang; Chunguang Wang; Zongshu Zhang; Xinyue Li; Tie Zhang (Poultry Science, 2023)
ABSTRACT: Infectious bursal disease (IBD) is a highly contagious viral disease caused by infectious bursal disease virus (IBDV) in chickens. The consequent immunosuppression and secondary infection affect the healthy development of chicken industry. In this study, specific primers and probes were screened in the conserved region of IBDV VP2 gene sequence, and reverse transcription-recombinase-aided amplification (RT-RAA) was combined with lateral flow dipstick (LFD) for establishing RT-RAA-LFD method for detection of IBDV in chickens. The reaction conditions of RT-RAA-LFD assay were optimized, and the specificity, sensitivity, and repeatability were verified. The results showed that the RT-RAA-LFD method could amplify the IBDV target fragment at 37°C for 15 min, and the required primer and probe concentration was 1,250 nmol/L. The detection results were directly observed by the dipstick, the lowest detectable limit (LDL) for IBDV was 10 copies/μL, and there was no cross reaction with several common immunosuppressive pathogens in poultry. The total coincidence rate of sample test results between RT-RAA-LFD and reverse transcription-polymerase chain reaction (RT-PCR) was 95.83%. Due to advantages of high sensitivity, strong specificity, easy operation, fast detection, the established RT-RAA-LFD method can provide some technical support and new solutions for local laboratory to detect IBDV.